Libyan Foreign Policy: A Study on Sources of Legitimacy during the period (1951-2011) - سعيد خطاب درمان, ولاء الدين; مفتاح فرج دخيل, عماد (Dirasat in Economics and Business, 2024)
This study aims to investigate the sources of Libyan foreign policy by looking at the legal sources of Libyan foreign policy in two different historical eras: the first of which extended for eighteen years, and the second period extended for more than forty years. The study explained how both systems: the monarchy and the republican and Jamahiriya political systems formulated the sources of Libyan foreign policy and the extent of their differences in their presentation in the state's foreign policy-making for both eras. It was necessary for us to get acquainted with the sources of Libyan foreign policy in both eras, to search and address the constitutions and documents in which the sources of Libyan foreign policy were mentioned during the period of the monarchy (1951-1969), as well as in its sources during the subsequent period (1969-2011.(